The Significance of Improving Faculty Performance through Motivation and Work Culture Implementation of a Website-Based Application System - Veronika, Trisni Wulandari; Rokhman , Fathur; Raharjo, Tri Joko; Arief, Sandy (Universitas Negeri Semarang, 2025)
Digital transformation in higher education has become a significant catalyst in improving the quality of academic services and the effectiveness of lecturer performance. This study aims to develop and test an integrative framework model that measures the relationship between work motivation, organizational culture, and lecturer performance, with digital technology as a moderating variable. Using a quantitative approach and Structural Equation Modeling (SEM) analysis, this study involved 303 lecturers from Semarang State University (UNNES) as the primary respondents. The research instrument was developed through a literature review and expert validation, covering indicators of intrinsic and extrinsic motivation, collaborative work culture values, and the effectiveness of academic digital applications such as SIKADU, SIMPEG, and ELENA. The analysis results show that digital technology significantly strengthens the relationship between motivation and work culture and improves lecturer performance. These findings provide theoretical contributions to the development of digital-based measurement instruments and practical contributions to higher education institutions in designing strategic policies that support the achievement of SDG 4 (Quality Education) and SDG 9 (Innovation and Infrastructure).